Raziskovanje bralnih navad in bralne kulture slovenskih knjižničarjev - Fras Popović, Sabina (Organizacija znanja, 2025)
The paper describes the methodology of a study of reading habits and reading culture of librarians and library management in Slovenian libraries, which is a part of a broader survey in the project Reading role models: reading habits of professional staff in kindergartens, schools and faculties and public libraries – i.e. a study of all professionals involved in and influencing reading literacy and reading culture, as well as of students for these professions. The survey uses mixed methodology: a survey and a focus group. As this research is still ongoing, this paper primarily describes the methodology of the first part, survey (instruments, sampling), some of the challenges, especially related to the non-existent data on the population of Slovenian librarians and library management, and basic findings. The focus group method is still under development and therefore only its basic starting points are given.
Keywords: bralne navade; knjižničarji; librarians; library management; methodology; metodologija; reading habits; Slovenia; Slovenija; vodstvo knjižnic